Pengaruh Pengaruh Audit Operasional dan Pengendalian Internal Terhadap Efektivitas Pelayanan Pada Perusahaan Daerah Air Minum (PDAM) Tirtanadi Kota Medan - Ansy, Dayat; Muhammad Arif; Nurwani (Ali Institute of Research and Publication, 2024)
The research aims to determine the influence of operational audits and internal control on service effectiveness at the Regional Drinking Water Company (PDAM) Tirtanadi, Medan City. This research uses quantitative research methods with data collection techniques using questionnaires from a sample of 40 employees in the Internal Supervisory Unit, Management Systems Division, Human Resources Division and Waste Water Services Operational Division and uses saturated sampling techniques. Data analysis uses multiple linear regression methods and hypothesis testing. The research results are based on the partial test hypothesis with a significant figure of 5% with a table of 2.026 showing that the Operational Audit variable has a positive and significant effect on the effectiveness of company services which shows tcount>ttable with variable X1 (3.287>2.026) and the Internal Control variable has a positive and significant effect on the effectiveness of company services which shows tcount>ttable with variable X2 (2,141>2.026). The research results from the simultaneous test hypothesis with a significant figure of 5% with Fcount of 10.224 and Ftable of 3.245 show that Fcount>Ftable (10.224>3.245) where Operational Audit and Internal Control have a joint (simultaneous) and significant effect on Service Effectiveness in the Company Tirtanadi Regional Drinking Water (PDAM) Medan City.